2007
DOI: 10.1037/1072-5245.14.2.142
|View full text |Cite
|
Sign up to set email alerts
|

Role conflict and burnout: The direct and moderating effects of political skill and perceived organizational support on burnout dimensions.

Abstract: Drawing from previous research on the effect of role conflict on burnout and the Conservation of Resources theory, the authors propose that individual differences in political skill and perceptions of organizational support will be negatively related to burnout and will also moderate the relationship between perceived role conflict and burnout. In a sample of 120 professional employees, political skill was associated with less depersonalization and feelings of reduced personal accomplishment and moderated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
163
1
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(188 citation statements)
references
References 60 publications
8
163
1
16
Order By: Relevance
“…This suggests that enhancing perceived organizational support will protect teachers from burnout. This is consistent with the findings of Kinman et al (2011) andJawahar et al (2007) who also reported an inverse association between workplace social support and emotional exhaustion and depersonalization among employees in human-service jobs.However, POS failed to moderate the associations between surface acting and emotional exhaustion; deep acting and emotional exhaustion; surface acting and depersonalization; and deep acting and depersonalization. Therefore, hypotheses 3a, 3b, 3c and 3d were not confirmed.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that enhancing perceived organizational support will protect teachers from burnout. This is consistent with the findings of Kinman et al (2011) andJawahar et al (2007) who also reported an inverse association between workplace social support and emotional exhaustion and depersonalization among employees in human-service jobs.However, POS failed to moderate the associations between surface acting and emotional exhaustion; deep acting and emotional exhaustion; surface acting and depersonalization; and deep acting and depersonalization. Therefore, hypotheses 3a, 3b, 3c and 3d were not confirmed.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are not in harmony with previous studies that found a moderating role of social support (e.g., Kinman et al, 2011;Moon et al, 2013). The findings were somewhat consistent with that of Jawahar et al (2007) who found that POS failed to moderate the relations between perceived role conflict and depersonalization. It is possible that the measurement of POS unidimensionally may have to some extent, contributed to findings in the current study.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Occupational organizations develop a new context in line with the new technological, economic and social changes that lead to a series of psychosocial problems that contribute to job stress and burnout which are considered as main problems affect employees' health (Jawahar et al, 2007). Economically, the organizations pay annually more than 60 billion dollars on workstress related diseases (Matteson & John 1987).…”
Section: Introductionmentioning
confidence: 99%